Validation of high-performance liquid chromatographic method for analysis of fluconazole in microemulsions and liquid crystals - Rocha e Silva, Hilris [UNESP]; Santos, Fernanda Kolenyak dos [UNESP]; Luz, Gabriela Marielli da [UNESP]; Chorilli, Marlus [UNESP]; Daflon Gremião, Maria Palmira [UNESP] (Universidade de São Paulo, Conjunto Químicas, 2014)
In recent decades, there has been a significant increase in the incidence of fungal diseases. Certain fungal diseases cause cutaneous lesions and in the usual treatment, generally administred orally, the drug reaches the site of action with difficulty and its concentration is too low. An approach much explored in recent years is the development of nanotechnology-based drug delivery systems, and microemulsions (ME) and liquid crystals (LC) are promising. ME and LC were developed with oleic acid or copaiba oil as the oil phase, propoxyl (5OP) ethoxyl (20 OE) cetyl alcohol as surfactant and water. An analytical method to assess the incorporation of fluconazole (FLU) in the systems under study was validated according to guidelines of the International Conference on Harmonization (ICH) guidelines and the Brazilian Food, Drug and Sanitation Agency (ANVISA). The method was conducted on a C18-RP column (250 x 4.6 mm i.d.), maintained at room temperature. The mobile phase consisted of acetonitrile and water (50: 50, v/v), run at a flow rate of 1.0mL/min and using ultraviolet detection at 210nm. The chromatographic separation was obtained with a retention time of 6.3min, and was linear in the range of 20-400 mu g/mL (r(2)=0.9999). The specificity showed no interference of the excipients. The accuracy was 100.76%. The limits of detection and quantitation were 0.057 and 0.172 mu g.mL(-1), respectively. Moreover, method validation demonstrated satisfactory results for precision and robustness. The proposed method was applied for the analysis of the incorporation of FLU in ME and LC, contributing to improve the quality control and to assure the therapeutic efficacy.

Nas últimas décadas, houve aumento significativo na incidência de doenças fúngicas. Certas doenças fúngicas provocam lesões cutâneas, sendo que no tratamento usual, geralmente administrado por via oral, o medicamento chega ao local de ação com dificuldade, em concentração muito baixa. Uma abordagem muito explorada nos últimos anos é o desenvolvimento de sistemas de administração de fármacos baseados em nanotecnologia, como as microemulsões (ME) e cristais líquidos (LC). ME e LC foram desenvolvidos com o ácido oleico ou óleo de copaíba como fase oleosa, álcool cetílico propoxilado (5 OP) e etoxilado (20 OE) como tensoativo e água. Método analítico para avaliar a incorporação de fluconazol (FLU) nos sistemas em estudo foi validado de acordo com as diretrizes da Conferência Internacional de Harmonização (ICH) e Agência Nacional de Vigilância Sanitária (ANVISA). O método foi desenvolvido empregando coluna C18-RP (250 x 4,6 mm id), mantida à temperatura ambiente. A fase móvel consistiu de acetonitrila e água (50:50, v/v), executado a uma taxa de fluxo de 1,0 mL/min e com detecção ultravioleta a 210 nm. A separação cromatográfica foi obtida com o tempo de retenção de 6,3min, e mostrou-se linear no intervalo de 20-400 µg/mL (r2=0,9999). Pelo estudo de especificidade, observou-se não interferência dos excipientes. A precisão foi 100,76%. Os limites de detecção e de quantificação foram 0,057 e 0,172 µg.mL-1, respectivamente. Além disso, a validação do método demonstrou resultados satisfatórios para a precisão e robustez. O método proposto foi aplicado para a análise da incorporação do FLU em ME e cristais líquidos, contribuindo para aumentar o controle de qualidade e garantir a eficácia terapêutica.
Keywords: Nanotehcnology; Microemulsions; Liquid crystals; High-performance liquid chromatography/qualitative analysis; Fluconazole; Nanotecnologia; Microemulsões; Cristais líquidos; Cromatografia líquida de alta eficiência/análise qualitativa; Fluconazol